Ecological network construction and optimization of typical resource-based regions, and strategies for the enhancement of multiple ecosystem services: Balancing function and structure - Shaoqing Wang; Yanling Zhao; Qiyuan Wang; He Ren; Shichao Zhu; Jiarui Cao (Ecological Indicators)
The extraction of mineral resources leads to the destruction of the surface landscape. To date, mining area restoration has mainly focused on specific projects; there is a lack of planning for large-scale ecological restoration of mining areas. The construction of ecological networks (ENs) is an effective solution to these problems. However, the application of the classic method of ENs construction in large-scale resource mining areas is not ideal. Moreover, the balance between the ecological function and topological structure of ENs is rarely considered. Therefore, this study proposed a new conceptual model and method for constructing ENs in resource-based regions and a novel optimization framework. The model combines ecological functions, topological characteristics and the degree of coordination between them to determine the optimization approaches for ENs under different ecological process scenarios. This study also examined the ecological and topological characteristics of ecological sources with or without mining areas (damaged ecological sources (DESs) and basic ecological sources (BESs)). The results revealed that the four ecosystem services in Liaoning Province exhibited increasing trends over the past 20 years. The average number of added pinch points and barrier points under different ecological process scenarios were 159 and 49, respectively, and the average number and total length of added corridors were 365 and 1911.51 km, respectively. The ecological functions of BESs performed better, but the topological structure and degree of coordination of DESs were better than those of BESs. The robustness of the optimized ENs showed a more gradual decreasing trend and greater “convexity”. The developed framework is applicable to other resource-based cities and regions and will help achieve sustainable development.